PREPARATION AND IN VITRO STABILITY STUDY OF 188Re-HEDP AS A BONE SEEKING RADIOPHARMACEUTICAL - Tripunoski, Toni; Mathe, Domokos; Balog, Lajos; Ugrinska, Ana; Chochevska, Maja; Stojanoski, Sinisha; Stanojevska, Elena; Manevska, Nevena; Grozdanovski, Toni; PopGjorceva, Daniela (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
The majority of patients with bone metastases will require some kind of therapy for bone pain palliation with the objective of improving the quality of live(1). Bone seeking radiopharmaceuticals emitting beta particles have been used for palliation of bone metastases. Recently, scientists propose a slightly different radionuclide, 188 Re that shows such promise for treating primary and metastatic tumors as a radiopharmaceutical 188 Re-HEDP. 188 Re-HEDP is a chemical complex of a bisphosphonate ligand with an incorporated atom of radioactive 188 Re. Bisphosphonates are ligands that contain the P-C-P bond which makes the molecules resistant to breakdown by enzymatic hydrolysis and are chemically very stable. In this study, we showed the conditions for the labeling of HEDP with 188 Re, and the in vitro stability of the radiopharmaceutical complex. 188 Re-HEDP is intended for the treatment of patients whose condition often requires for the therapeutic dose to be transported to the institution where the patient is hospitalized. Our stability study is performed in order to determine the optimal storage conditions of the radiopharmaceutical if it is not applied to a patient immediately after preparation. The results of radiochemical purity of 188 Re HEDP using ITLC quality control technique was above 98%. The stability study for 188 Re HEDP stored at different ambiental conditions showed that the complex is most stable in the first 3 hours after preparation, if it is stored at +4 o C in the dark. It can be concluded that the prescribed preparation conditions (composition and concentration of chemical components, temperature and incubation time) are optimal for the formation of high percentage and stable initial chelating complex of 188 Re-HEDP. Keywords: bone pain palliation, radionuclide therapy, radiopharmaceuticals, Rhenium-188.